Inclusive charged and neutral particle multiplicity distributions in chi(cJ) and J/psi decays - Çetin, Serkant Ali (Amer Physical Soc., 2020)
Using a sample of 106 million psi(3686) decays, psi(3686) -> gamma chi(cJ) (J = 0, 1, 2) and psi(3686) -> gamma chi(cJ), chi(cJ) -> gamma J/psi (J = 1, 2) events are utilized to study inclusive chi(cJ )-> anything, chi(cJ )-> hadrons, and J/psi( )-> anything distributions, including distributions of the number of charged tracks, electromagnetic calorimeter showers, and pi(0)s, and to compare them with distributions obtained from the BESIII Monte Carlo simulation. Information from each Monte Carlo simulated decay event is used to construct matrices connecting the detected distributions to the input predetection "produced" distributions. Assuming these matrices also apply to data, they are used to predict the analogous produced distributions of the decay events. Using these, the charged particle multiplicities are compared with results from MARK I. Further, comparison of the distributions of the number of photons in data with those in Monte Carlo simulation indicates that G-parity conservation should be taken into consideration in the simulation.
24 pages